Pelatihan Pembuatan Portofolio Bisnis dalam Meningkatkan Brand Awareness UKM Bidang Kuliner - Hermawati, Lisa; Yulitiawati, Yulitiawati; Dona, Eka Meiliya; Gultom, Angga Wibowo; Rahayu, Sri (Penerbit Goodwood, 2025)
Purpose: The training aimed to enhance brand awareness among culinary SMEs in South Sumatra by equipping them with effective marketing strategies to attract consumer attention in a competitive market. Methodology/approach: Using a literature-based and systematic approach, the two-day training focused on business portfolio creation, effective communication, and social media promotion. It involved 34 SMEs from 17 districts/cities and emphasized branding, customer relationships, and innovation. Results/findings: The training led to significant improvements in product recognition and customer interest. It also helped participants build a positive brand image and gain practical skills and strategic insights to strengthen competitiveness and sustainability. Conclusions: The training successfully equipped culinary SMEs with the ability to create professional business portfolios and strengthen brand identity. Participants are expected to integrate these tools into their marketing strategies to support growth and competitiveness. Limitations: The findings may not represent all culinary SMEs in South Sumatra and rely on the honesty and engagement of participants, which may affect data validity. Contribution: The training contributed by providing SMEs with essential skills for developing business portfolios and improving marketing strategies, thus enhancing brand awareness and long-term sustainability in a competitive environment.